Validity and Reliability Test of Vitiligo Quality of Life Index (VitiQoL) Indonesian Version in Vitiligo Patients - Jeffrey Giantoro; Fajar Waskito; Sunardi Radiono (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Vitiligo is a multifactorial skin disorder that causes depigmentation. Vitiligo can affect a patient's quality of life due to aesthetic issue. The prevalence of vitiligo in the world is 0.5 – 1.0%. An instrument for measuring the quality of life that is specific to vitiligo patients in Indonesia is required. Purpose: This study aims to translate the Vitiligo Specific Quality of Life (VitiQoL) questionnaire into Indonesian: and assess the validity and reliability of the Indonesian language VitiQoL as a quality of life instrument. Methods: An observational method with analytical survey and cross-sectional approach was conducted on 48 vitiligo patients at Sardjito General Hospital Yogyakarta in May – September 2021. The research was carried out in 3 stages. The first stage was the translation of VitiQoL into Indonesian and then back into English. The second and third stages were measuring the validity and reliability of the VitiQoL Indonesian version. Result: The validity test using Pearson product moment showed that the average correlation coefficient for each question is 0.683. Reliability test using Cronbach's alpha of 0.924 VitiQoL. VitiQoL has 3 domains, namely limited participation, stigma, and behavior. The correlation of each domain has a value range of 0.756 - 0.918 with a variation of Cronbach's alpha value per item ranging from 0.808 - 0.89. The limited participation domain (84.2%) has the largest contribution to the value of quality of life. Conclusion: The Indonesian language VitiQoL as an instrument with good validity and reliability can be used to measure the quality of life of vitiligo patients in Indonesia.